From hinterland to heartland: Knowledge and market insecurity are barriers to crop farmers using sustainable soil management in Guyana - Melville, Jonathan L.; Kuznesof, Sharron; Franks, Jeremy R. (Frontiers in Sustainable Food Systems, 2023)
The coastal plains dominate agricultural production in Guyana. However, the hinterland is seen as an emerging agricultural frontier. The coastal and hinterland regions have differing agro-climatic conditions, but share immediate climate change and environmental degradation pressures, including soil degradation. Even though adaptation is prioritized over mitigation in Guyana, soil-focused farming, otherwise known as sustainable soil management (SSM), provides a system that allows synergies between these two aspects of climate-smart agriculture. In-depth telephone interviews were conducted with seventeen (17) farmers located in coastal and hinterland regions to pilot a bottom-up approach for SSM practices by assessing underlying physical and psycho-social facilitators and barriers. Inductive-derived thematic analysis identified lack of education and training as severe limitations to the capabilities of farmers to practise SSM. Where hinterland farmers are more emotive and value-driven about their environment, coastal farmers, instead, tend to prioritize access to markets and gaining favourable prices for their commodities. A weak marketing environment is seen as a binding constraint of sustainable intensification as surplus goods attract low prices. Stronger linkages to dynamic markets, as well as increased investment opportunities are needed for sustainable farming to become feasible. Therefore, social capital must be strengthened before any natural capital is improved under Guyana’s various agro-environmental policies.